2013
DOI: 10.1073/pnas.1300962110
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide diel growth state transitions in the diatom Thalassiosira pseudonana

Abstract: Marine diatoms are important primary producers that thrive in diverse and dynamic environments. They do so, in theory, by sensing changing conditions and adapting their physiology accordingly. Using the model species Thalassiosira pseudonana, we conducted a detailed physiological and transcriptomic survey to measure the recurrent transcriptional changes that characterize typical diatom growth in batch culture. Roughly 40% of the transcriptome varied significantly and recurrently, reflecting large, reproducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
162
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 58 publications
17
162
1
Order By: Relevance
“…To explore DPH function, we first monitored DPH expression by RT-qPCR in P. tricornutum cells grown under 12-h-ligh/12-h-dark cycles or maintained in prolonged darkness for 48 h. This revealed that Pt-DPH transcripts exhibited a pronounced diurnal rhythmic expression pattern, with an accumulation at the end of the light period, as observed for Tp-DPH (Ashworth et al, 2013) (Figure 2A). In contrast, in prolonged darkness, Pt-DPH mRNA levels remained at a constant low level (Figure 2A).…”
Section: Pt-dph Expression Is Light Regulatedmentioning
confidence: 77%
“…To explore DPH function, we first monitored DPH expression by RT-qPCR in P. tricornutum cells grown under 12-h-ligh/12-h-dark cycles or maintained in prolonged darkness for 48 h. This revealed that Pt-DPH transcripts exhibited a pronounced diurnal rhythmic expression pattern, with an accumulation at the end of the light period, as observed for Tp-DPH (Ashworth et al, 2013) (Figure 2A). In contrast, in prolonged darkness, Pt-DPH mRNA levels remained at a constant low level (Figure 2A).…”
Section: Pt-dph Expression Is Light Regulatedmentioning
confidence: 77%
“…These findings suggest that hypomethylation may play an important role in regulating the expression of sets of genes (e.g., transporters) under a given set of environmental conditions (Veluchamy et al, 2013). Additionally, Ashworth et al (2013) identified transcription factors that putatively control different regulatory networks in T. pseudonana, resulting in co-expression of thousands of genes in response to different environmental conditions including the day/night cycle and the transition from nutrient-replete growth to nitrate limitation. Koester et al (2012) found evidence that transcription factors within T. pseudonana are under positive selection, implying that mutations within the genes encoding transcription factors convey adaptive phenotypes.…”
Section: Discussionmentioning
confidence: 90%
“…Despite these general commonalities, relatively few othologs shared by the two diatoms display similar transcriptional patterns under nitrogen limitation (Maheswari et al, 2010). Some of the genes with shared transcriptional patterns are involved in nitrogen assimilation (e.g., nitrate/nitrite reductase) and the first step of the urea cycle (e.g., carbamoyl phosphate synthetase) Allen et al, 2011;Hockin et al, 2012;Ashworth et al, 2013). However, the remainder of the urea cycle genes and genes encoding urease and nitrate and ammonium transporters, are transcribed differently by the two diatoms; e.g., urease gene expression is elevated in T. pseudonana under nitrate limitation vs. nutrient-replete conditions, whereas this gene exhibits constitutive expression in P. tricornutum (Allen et al, 2011;Hockin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Subcellular localization data were inferred from annotated diatom gene sequences and the available literature (Armbrust et al, 2004;Bowler et al, 2008;Brown et al, 2009;Kinoshita et al, 2009;Allen et al, 2011). A caveat to the following discussion is that variation in diurnal timing (for BFS) could have transcriptome-wide effects on relative enrichment (Ashworth et al, 2013;Chauton et al, 2013). In contrast to ammonium and urea transporters discussed in the previous section, nitrate transporters were less abundant in the more oceanic BFS community, despite high NO 3 − levels in the water column (Figure 1b).…”
Section: Diatom Nitrogen Metabolism Is Flexible Among Habitatsmentioning
confidence: 97%